The Gambia: a haven for refugees? - Zanker, F (Refugee Studies Centre, University of Oxford, 2018)
Although not usually thought of as a haven of refugee protection, the Gambia has a fairly sizeable refugee population and some sophisticated legal frameworks and protection mechanisms. However, the political context of its refugee protection should not be underestimated.